Independence of the judiciary: a study of a recent trend / Mohd. Daud Mohd. Nor - Mohd. Nor, Mohd. Daud (Faculty of Law, 1987)
The Judiciary in Malaysia often has to raterate its independence of the Executive. In other parts of the world this would have been an occasion for serious concern as it would seem to imply that the government is attempting to control the judges. Actually the local Judiciary is continuing a dialogue with sections of the public which feel it has not stood up adequately to protect fundamental rights against executive incursions. Since Independence thirty years ago. the government has detained without trial political prisoners loosely— termed as 'subversives' under the Internal Security Act 1960. Many cases came up for hearing in the courts but few petitioners, if any, were released from detention. The general feeling among lawyers is that the judges could have done more in upholding basic rights. This writer agrees with the general criticism but is also of the opinion that the Judges have the difficult task of balancing public interests against individual's interests. This paper seeks to show that their pro-government decisions are actuated by the interest for the general security of the public, which may be harsh to the individual. "his has been the trend since Independence.